Long-range ordered TiO2/Au hollow urchins: topology control for maskless electrodeposition. Issue 48 (8th December 2020) - Kandjani, Ahmad Esmaielzadeh; Sabri, Ylias M.; Coyle, Victoria E.; Harrison, Christopher J.; Korcoban, Dilek; Canjeevaram Balasubramanyam, Ram Kumar; Jones, Lathe A.; Field, Matthew R.; Bhargava, Suresh K.
Abstract : We present a novel approach for fabricating multicomponent ordered nanostructures using colloidal lithography and electrodeposition techniques, enabling maskless, targeted and uniform material deposition. Abstract : We present a novel approach for fabricating multicomponent ordered nanostructures using colloidal lithography and electrodeposition techniques, enabling maskless, targeted and uniform material deposition. As an example of the capability of our approach to develop low-cost ordered complex structures, we fabricated long-range ordered crystals (LROCs) of titania/gold urchins. The fabrication process involved four steps: (i) development of non-close-packed polystyrene monolayer templates; (ii) fabrication of supporting titania micro-shells via chemical vapor deposition on the templates; (iii) evaporation of a thin film of gold to form a conductive layer, and (iv) electrodeposition of a secondary component, gold nano-spikes, localized on each colloid in the LROC. We demonstrated that the electrodeposition can be localized on 200 nm thick micro-shell nanostructures, and the size of gold nano-spikes can be controlled in length between 100 nm and 1.5 μm. This length control leads to a versatile class of composite materials where an underlying micro-shell structure, titania in this example, and electrodeposited nanostructures, gold nano-spikes, have direct access to the surrounding medium. This novel method provides both self-cleaning and sensing multifunctionalities with high repeatability and control due to the long-range uniformity of the structures created.